Comparison of allergenic extracts from different origins: the value of the FDA’s bioequivalent allergy unit (BAU) - Passalacqua, Giovanni; Pfaar, Oliver (Expert review of clinical immunology, 2016)
Introduction: Allergy immunotherapy (AIT) is the only disease-modifying intervention for the treatment of allergic diseases. The clinical effectiveness of AIT is clearly dose-dependent, so it is important that clinicians can assess and compare the potency of the various products available. However, this is not possible in practice, because manufacturers use different methods to determine potency. Therefore, a clear need exists for adoption of a ‘gold-standard’ measure of allergenicity. The bioequivalent allergy unit (BAU) is thus far the only allergen unit approved by a regulatory agency (the US Food and Drug Administration), with European regulatory authorities yet to adopt a common unit.Areas covered: Using PubMed, we performed a review of the literature on measures of allergen extract potency, use of the BAU, and BAU assessment for grass pollen tablets.Expert commentary: There is an obvious benefit to allergists and patients for having a single, comparable unit across products, and we strongly support the adoption of a single, ‘gold-standard’ unit of measurement for all products. Use of the BAU allows a clear comparison of the potency of allergen products from different manufacturers, and enables better understanding of the potential reasons for any differences in administration and dosing protocols between these products.